SPECIFIC USE OF INFORMATION TECHNOLOGIES IN A BLENDED MODEL OF TEACHING FOREIGN LANGUAGES - Natalia A. Kameneva; Liudmila V. Zenina (Статистика и экономика, 2016)
The article determines the role and analyzes specificity of the use of information technology in a mixed model of learning foreign languages in higher educational institutions. The authors also describe such forms of e-learning as a webinar, seminar videos, video conferencing, case-technology. The ways of overcoming difficulties in learning foreign languages, which the students can face when using distance learning technologies, are indicated. The positive experience of using E-learning System «Virtual Campus» in the teaching foreign languages at the Moscow State University of Economics, Statistics and Informatics is mentioned.